2016
DOI: 10.1021/acs.est.6b00255
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Behavior of Graphene Oxide on Nanocrystallined Mg/Al Layered Double Hydroxides: Batch Experimental and Theoretical Calculation Study

Abstract: Graphene oxide (GO) has attracted considerable attention because of its remarkable enhanced adsorption and multifunctional properties. However, the toxic properties of GO nanosheets released into the environment could lead to the instability of biological system. In aqueous phase, GO may interact with fine mineral particles, such as chloridion intercalated nanocrystallined Mg/Al layered double hydroxides (LDH-Cl) and nanocrystallined Mg/Al LDHs (LDH-CO3), which are considered as coagulant molecules for the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
117
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 284 publications
(120 citation statements)
references
References 56 publications
2
117
0
1
Order By: Relevance
“…Hence, the understanding of the physical and chemical behavior of GO in the natural environment is significantly to evaluate its toxicity to human beings. From the literature survey, the efficient way to lower the GO concentration in water is the coagulation of GO, which forms large agglomerates that can be easily separated by aggregation, filtration or centrifugation121516. Thereby, the coagulation kinetics and stability of GO have been extensively investigated in the literatures4171819, and the results showed that the stability of GO in aqueous solution was strongly influenced by ionic strength and pH values.…”
mentioning
confidence: 99%
“…Hence, the understanding of the physical and chemical behavior of GO in the natural environment is significantly to evaluate its toxicity to human beings. From the literature survey, the efficient way to lower the GO concentration in water is the coagulation of GO, which forms large agglomerates that can be easily separated by aggregation, filtration or centrifugation121516. Thereby, the coagulation kinetics and stability of GO have been extensively investigated in the literatures4171819, and the results showed that the stability of GO in aqueous solution was strongly influenced by ionic strength and pH values.…”
mentioning
confidence: 99%
“…Layered double hydroxides (LDHs) are kinds of lamellar inorganic materials which can be described by the general formula [M 1 – x 2+ M x 3+ (OH) 2 ] x + (A n– ) x /n · m H 2 O. M 2+ and M 3+ are divalent (e.g., Mg 2+ , Co 2+ , Ni 2+ , Zn 2+ , Cu 2+ ) and trivalent cations (e.g., Al 3+ , Fe 3+ , Ga 3+ ), respectively; A n– is interlayer gallery anion (e.g., CO 3 2− , Cl − , NO 3 − , SO 4 2− ); and x is the molar ratio of M 3+ /(M 2+  + M 3+ ) and the layer charge will depend on the M 2+ /M 3+ ratio91011. By heating to 450–500 °C, LDHs can be converted into mixed metal oxides (MMOs), which exhibit fine dispersion of metal cations and high surface area.…”
mentioning
confidence: 99%
“…The spectra of LDH showed characteristic peaks: 3526 cm −1 (O—H groups) and 1384 cm −1 (NO 3 − stretching vibration) 21. LDH‐VP16 showed 1610 cm −1 (C=O stretch of carboxyl methyl) and 1485 cm −1 (C=C stretching in the backbone of the aromatic phenyl ring) similar to VP16 and 3526 cm −1 (O—H groups) and 1384 cm −1 (NO 3 − stretching vibration) similar to LDH.…”
Section: Resultsmentioning
confidence: 99%